Factors Influencing Adoption of Improved Production Technologies among Irish Potato (Solanum Tuberosum) Farmers in Bokkos Local Government Area of Plateau State, Nigeria - E. D. Udoh; E. O. Samson; I. E. Ema; B. I. Ogar (Journal of Applied Sciences and Environmental Management)
This study examined factors influencing the adoption of improved production technologies among Irish potato farmers in Bokkos Local Government Area, Plateau State, Nigeria. A total of 160 farmers were surveyed using a structured questionnaire. The data were analyzed using descriptive statistics, Likert scales, and logit regression. The findings show that most farmers are relatively young, with 47% aged 31–40 years, 67% male, and 90% married. Additionally, 44% have completed secondary education, and 61% have 6–10 years of farming experience. Farmers demonstrated strong awareness of technologies for appropriate harvesting (mean = 3.44), timely weeding (mean = 3.41), and optimal planting dates (mean = 3.25). However, awareness was lower for seed treatment (mean = 1.99) and recommended plant spacing (mean = 2.08). Adoption rates reflected these trends, with high adoption for harvesting and weeding technologies but low utilization of seed treatment and proper spacing. Logit regression analysis identified age, educational status, annual income, farming experience, and extension contact as significant predictors of adoption. Major constraints included the high cost of technology (69%), inadequate extension contact (61%), and limited credit access (48%). The study recommends affordable credit options, enhanced extension services, simplified technologies, and improved access to address these constraints. These measures are expected to increase productivity and improve farmers' livelihoods.